2005
DOI: 10.1007/s00213-005-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of adenosine and dopamine receptors inhibits the development of rapid tolerance to ethanol in mice

Abstract: Our results suggest that the rapid tolerance to ethanol-induced motor impairment in mice may be modulated by adenosine A1 receptors and dopamine D1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
(61 reference statements)
3
29
0
Order By: Relevance
“…In rodents, many studies using selective adenosine receptor agonists and antagonists have consistently demonstrated that adenosine receptors, localized in brain areas essential for motor control such as striatum, the cerebellum, and the motor cortex, are the primary site where adenosine modulates the incoordination induced by ethanol (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001). Additionally, we have recently demonstrated that the blockade of adenosine receptors inhibits the development of rapid tolerance to ethanol-induced motor impairment in mice (Batista et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In rodents, many studies using selective adenosine receptor agonists and antagonists have consistently demonstrated that adenosine receptors, localized in brain areas essential for motor control such as striatum, the cerebellum, and the motor cortex, are the primary site where adenosine modulates the incoordination induced by ethanol (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001). Additionally, we have recently demonstrated that the blockade of adenosine receptors inhibits the development of rapid tolerance to ethanol-induced motor impairment in mice (Batista et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…In humans, the nonselective adenosine receptor antagonist caffeine reduces sleepiness and psychomotor performance impairment produced by moderate-to-high ethanol doses (Franks et al, 1975;Fillmore and Vogel-Sprott, 1995;Liguori and Robinson, 2001;Drake et al, 2003). In rodents, adenosine receptors seem to modulate some of the pharmacological properties of ethanol, such as sedative/ hypnotic effects (El Yacoubi et al, 2003), motor incoordination (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001), and development of rapid tolerance to ethanolinduced motor impairments (Batista et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism of the final response of the dimerized activation of these receptors is that ethanol desensitizes receptors linked to the stimulatory G protein ( subunit), modulating the coupling of D 2 with the AC pathway, which may be related to PKA (Yao et al, 2001;Batista et al, 2005). Inoue et al (2007) found that co-activation of A 2A and D 2 mediates the transient interaction between nicotine and ethanol, showing an indirect relationship with the cholinergic system, where the use of antagonists of this co-activation can prevent, mitigate or even reverse the use of smoke and ethanol.…”
Section: Ethanol and Adenosine Relation In Different Neurotransmissiomentioning
confidence: 99%
“…Thus, the effect size for caffeine in this parameter is greater than for theophylline (see table 2). While low to moderate doses of caffeine (3-30 mg/kg) have demonstrated not to produce motor incoordination in mice in the rotarod [22,44], the present results on moderate to high doses of caffeine are in agreement with a study that evaluated the stumbling frequency in the holeboard test as a measure of motor coordination after moderate to high doses of caffeine (30-120 mg/kg), and demonstrated a dose-dependent increase in stumbling frequency [25]. Our data on theophylline are also consistent with a previous study showing that intraventricular administration of theophylline (150 µg/5µl) in mice did not affect endurance on the rotarod [45].…”
Section: Discussionmentioning
confidence: 97%
“…Although ethanol is generally classed as a sedative-hypnotic and caffeine is considered to be a minor stimulant, both drugs are able to stimulate locomotor activity in rodents at some dose [43][44][45][46][47][48] , typically with bell-shaped (or inverted-u) dose response functions. Rodents (more in mice than rats)…”
Section: 42mentioning
confidence: 99%